THE INFLUENCE OF MOTIVATION, JOB EDUCATION, TOTAL PARTICIPATION, AND LEADERSHIP ON EMPLOYEE PERFORMANCE ASSESSMENT WITH JOB SATISFACTION AS AN INTERVENING VARIABLE AT PTPN 4 REGIONAL 1 RANTAUPRAPAT PROMISE GARDEN - Stefen Daniel Berkat Hutabarat; Kholilul Kholik; Muhammad Toyib Daulay (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2026)
This study analyzes the influence of work motivation, job education, total participation, and leadership on employee performance assessment, with job satisfaction as an intervening variable, at PTPN IV Regional 1 Janji Rantauprapat Garden. The labor-intensive plantation sector faces challenges in enhancing employee performance, which is influenced by factors such as motivation, training, employee involvement, and leadership styles. This research employs a quantitative approach, utilizing a census method that included all 127 permanent employees. Data analysis was conducted using Structural Equation Modeling (SEM) based on Partial Least Squares (PLS) with the aid of SmartPLS 4.0 software. The findings indicate that none of the exogenous variables (work motivation, job education, total participation, and leadership) had a significant direct or indirect influence on either job satisfaction or employee performance. Furthermore, job satisfaction was not found to significantly mediate the relationship between the exogenous variables and employee performance. Additionally, the research model demonstrated low predictive relevance (Q-Square value), suggesting that it does not adequately explain the variations in job satisfaction and employee performance within this specific context. This study concludes that the hypothesized relationships were not significant in this setting, highlighting the need for further research considering other factors or different methodologies to understand employee performance drivers.